A importância da leitura e a escrita para o 3° ano no ensino fundamental menor - OLIVEIRA, Lília Soraia Amaral (2024)
Such research has as its theme: The importance of reading and writing for the 3rd year of lower primary education took place in the Municipal Primary School Alderman Mark Martins Magno, seeking to answer the problem of how happens the inclusion of reading and writing in teacher practice this mode of education that work at this school, verifying the design that permeates the practices of the actors involved in the learning process and discussing their practice in educating readers. It was noticed during the research that some factors have contributed to the teaching learning process is not made real in student learning, among these: the lack of interest of students and failure in the literacy process. We believe that the expected results were achieved because it was understood that there are still many difficulties involved in the process of reading and writing in the experience of the students, thus hindering his learning and somehow inhibiting their actions.